Fesyen Akademik sebagai Alternatif Kebaruan dalam Budaya Populer - Denissa, Lois (PANGGUNG, 2019)
ABSTRACTFashion is not enough just to act as a protective body for weather,disease disorders,neatness and decency reasons. Fashion in its development has proven to be a medium of communication that expresses taste, attitude, gender, identity, trend, ethnicity, social class and culture. Research that uses analytical descriptive method has expanded the communicative function of fashion. The mass media has become a synergistic industrial agent in giving persuasion to modern women both in the city and region. Women tend to be enamored with the flow of ads in order to appear up to date and fetish ideal body like women in advertising. Advertising modelsare always displayed with beautiful, charming features highlight the sensual body. The academic fashion that puts research and creativity as the basis of work has countered the fashion advertising. Academic fashion contributes to popular culture by creating innovation that inspire modern women with layered messages.Keywords: AcademicFashion, Communication,Layered Message , Popular CultureABSTRAKFesyen sebagai busana tidak cukup hanya berperan sebagai pelindung tubuh atas gangguan cuaca dan penyakit, atau alasan kerapian dan kesopanan. Fasyen dalam perkembangannya terbukti telah menjadi media komunikasi yang mengungkapkan selera, sikap, gender, identitas, tren, etnisitas, kelas sosial dan budaya. Penelitian yang menggunakan metode diskriptif analitis ini memperlebar fungsi komunikatif fesyen. Media massa telah menjadi agen industri yang sinergis dalam memberi bujuk rayu kepada perempuan modern baik di kota maupun di daerah. Perempuan cenderung terpikat mengikuti arus iklan agar dapat tampil up to date dan menggemari pemujaan akan tubuh yang ideal layaknya perempuan dalam iklan. Model iklan selalu disiasati dengan paras cantik, menawan dan menonjolkan tubuh yang sensual. Fesyen akademik yang menempatkan penelitian dan kreativitas sebagai basis berkarya telah membantah fesyen iklan. Fesyen akademik ikut mengisi budaya popular dengan menciptakan kebaruan yang mampu menginspirasi perempuan modern dengan pesan yang berlapis.Kata Kunci: Budaya Populer, Fesyen Akademik, Komunikasi, Pesan Berlapis